The modulation of motor contagion by intrapersonal sensorimotor experience. (15th June 2016) - Roberts, James W.; Katayama, Orion; Lung, Tiffany; Constable, Merryn D.; Elliott, Digby; Lyons, James L.; Welsh, Timothy N.
Highlights: Execution is interfered when observing incongruent movements. Underpinned by the presence of response-specific feedback. Modulate the inhibition of interference through intrapersonal sensorimotor experience. Sensorimotor experience may relate to the sense of agency. Abstract: Sensorimotor experiences can modify the internal models for action. These modifications can govern the discrepancies between predicted and actual sensory consequences, such as distinguishing self- and other-generated actions. This distinction may also contribute toward the inhibition of movement interference, which is strongly associated with the coupling of observed and executed actions. Therefore, movement interference could be mediated by the sensorimotor experiences underlying the self-other distinction. The present study examined the impact of sensorimotor experiences on involuntary movement interference ( motor contagion ). Participants were required to complete a motor contagion paradigm in which they executed horizontal arm movements while observing congruent (horizontal) or incongruent (vertical) arm movements of a model. This task was completed before and after a training protocol in which participants executed the same horizontal arm movements in the absence of the model stimuli. Different groups of participants trained with or without vision of their moving limb. Analysis of participants who were predisposed to motor contagion (involuntary movement interference during the observation of incongruent movements) revealed that the no vision group continued to demonstrate contagion at post-training, although the vision group did not. We propose that the vision group were able to integrate the visual afferent information with an internal model for action, which effectively refines the ability to match self-produced afferent and efferent sources of information during response-execution. This enhanced matching allows for a better distinction between self and other, which in turn, mediates the inhibition of motor contagion.